Temperature dependent 1/f noise characteristics of the Fe/GaN ferromagnetic Schottky barrier diode. (7th September 2015) - Kumar, Ashutosh; Nagarajan, S; Sopanen, M; Kumar, V; Singh, R
Abstract: The temperature dependent current–voltage ( I – V ) and 1/ f noise characteristics of the Fe/GaN ferromagnetic metal–semiconductor (FM/SC) Schottky barrier diode are presented. At 300 K, an ideality factor of 1.3 and a barrier height of 0.92 eV suggested thermionic emission as the dominant current transport mechanism at the FM/SC interface. The ideality factor increased to 3.4 while the barrier height decreased to 0.36 eV at 100 K, indicating the presence of other current transport mechanisms in addition to thermionic emission. The spectral power density of current fluctuations, is measured as a function of frequency in the temperature range 100–300 K, where followed with γ close to unity. A 1/ f type of noise spectrum at each temperature in the range 100–300 K is attributed to the existence of barrier inhomogeneities at the Fe/GaN interface. The inhomogeneous nature of Fe/GaN is also revealed from the temperature dependent I – V characteristics. From temperature dependent I – V and 1/ f noise measurements, it is found that current transport is limited by diffusion currents below 200 K, resulting in an increase in noise with temperature. Above 200 K, thermionic emission is the dominant current transport mechanism and noise behavior is affected by barrier inhomogeneities, resulting in a decrease in noise with an increase in temperature.